PENGARUH PENAMBAHAN LIMBAH PADAT ABU TERBANG BATUBARA(FLY ASH) TERHADAP KEKUATAN TEKAN DAN POROSITAS GENTENG TANAH LIAT KABUPATEN PRINGSEWU - Puji Febriyansyah; . Tarkono; . Zulhanif (Jurnal Ilmiah Teknik Mesin, 2013)
Fly ash, chemicallyis analumino-silicamineral containing Ca, K, and Na elements, fly ash has amoderate to high bonding capacity characteristic , and has acement-forming properties. In this study the authors use the industrial fly ash coal waste as an alternative mixture of tile manufacture. The tiles manufactured by mixing clay, sand, water and fly ash. Then smoothed with ekstuder machine and forming kuweh then aerate for 3 days, before do the dieing process . Tile dried for 4 days, then do fumigation for 12 hours and followed by burning process for 12 hours . Testing is done for press and porosity testing in order to determine the presence/absence of the influence of the addition of rice husk ash/fly ash to clay tile in the Pringsewu Region.The results showed that there is compressive strength and porosity change compared to tiles without a mixture of fly ash . The optimum value for testing tap and porosity testing obtained on the tile with a mixture composition of fly ash is 5% to the value of the average compressive strength of 11,042 kPa and the mean porosity is17.27 % . The minimum value for testing tap and porosity obtained on tile without fly ash mixed with the mean compressive strength of 8,393 kPa and the mean porosity is 21,92 %Keywords : clay tile, coal fly ash, silica (SiO2), compressive strength, porosity